Addressing individual perceptions: An application of the unified theory of acceptance and use of technology to building information modelling. Issue 2 (February 2017) - Howard, Robert; Restrepo, Luis; Chang, Chen-Yu
Abstract: Building Information Modelling (BIM) is a technology with the potential to transform the construction industry, yet its proliferation remains stagnant. Existing research on BIM diffusion focuses on the industry, company, and project levels while disregarding the impact of perceptions at the individual level. This research aims to extend the Unified Theory of Acceptance and Use Technology (UTAUT) model to understand the perceptions that individuals have towards working with BIM. A survey was completed by 84 industry stakeholders and the results analysed against a modified UTAUT model that adds the variable of Attitude and employs moderators of Experience and Voluntariness. The results reveal that Performance Expectancy does not directly affect Behavioural Intention, signifying that BIM is perceived as an unrewarded addition to existing work processes. These findings evince the need to redefine strategies, policies, and incentive schemes in order to advance the acceptance of BIM in the U.K. and worldwide. Highlights: Universal Theory of Acceptance and Use of Technology applied to Building Information Modelling Study measures the perception of Building Information Modelling among industry practitioners Social Influence has the greatest impact on Behavioural Intention towards BIM Facilitating Conditions has the greatest impact on BIM User Behaviour Performance Expectancy did not significantly impact Behavioural Intention towards BIM